Impact of Noise Power Uncertainty on the Performance of Wideband Spectrum Segmentation - Tascioglu, Selcuk; Uereten, Oktay; Telatar, Ziya (Společnost pro radioelektronické inženýrství, 2010)
The objective of this work is to investigate the impact of noise uncertainty on the performance of a wideband spectrum segmentation technique. We define metrics to quantify the degradation due to noise uncertainty and evaluate the performance using simulations. Our simulation results show that the noise uncertainty has detrimental effects especially for low SNR users.
Keywords: Cognitive radio; spectrum sensing; wideband RF spectrum monitoring; noise uncertainty; Markov chain Monte Carlo